2017
DOI: 10.1080/14735903.2017.1402504
|View full text |Cite
|
Sign up to set email alerts
|

System of crop intensification for more productive, resource-conserving, climate-resilient, and sustainable agriculture: experience with diverse crops in varying agroecologies

Abstract: With continually increasing demand for food accompanied by the constraints of climate change and the availability and quality of soil and water, the world's farmers are challenged to produce more food per hectare with less water, and with fewer agrochemical inputs if possible. The ideas and methods of the system of rice intensification which is improving irrigated rice production are now being extended/ adapted to many other crops: wheat, maize, finger millet, sugarcane, tef, mustard, legumes, vegetables, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(60 citation statements)
references
References 41 publications
0
31
0
2
Order By: Relevance
“…The resulting crop diversity and high yields may be an adequate incentive for those who wish to adopt sustainable agricultural practices on a large scale, but had previously found them not to be financially rewarding [107]. Thus, incorporating underutilized indigenous and traditional crops into the production system will result in improved sustainability and resilience in the food system [102]. Figure 3 elicits and captures the transdisciplinary approach to re-orient and prioritize local indigenous agro-food systems, namely: (i) the creation of an alternative and diverse food system that empowers local smallholder famers; (ii) that caters to the nutritional health and livelihood of the resource poor; and, (iii) that addresses climate and environmental change impacts and builds resilience.…”
Section: Addressing Socio-economic and Environmental Concerns Throughmentioning
confidence: 99%
“…The resulting crop diversity and high yields may be an adequate incentive for those who wish to adopt sustainable agricultural practices on a large scale, but had previously found them not to be financially rewarding [107]. Thus, incorporating underutilized indigenous and traditional crops into the production system will result in improved sustainability and resilience in the food system [102]. Figure 3 elicits and captures the transdisciplinary approach to re-orient and prioritize local indigenous agro-food systems, namely: (i) the creation of an alternative and diverse food system that empowers local smallholder famers; (ii) that caters to the nutritional health and livelihood of the resource poor; and, (iii) that addresses climate and environmental change impacts and builds resilience.…”
Section: Addressing Socio-economic and Environmental Concerns Throughmentioning
confidence: 99%
“…Previous studies have suggested the suitability of landraces under Mediterranean semi-arid conditions (e.g., Giambalvo et al [30]), which can be relevant sources for sustainable agriculture in a CC context more suitable to adapt to future scenarios [61]. By cultivating landraces, we could also meet some sustainable crop intensification (SCI) practices described for a climate-resilient and sustainable agriculture [62], like the use of plants with vigorous early growth [63] and reducing the needs of herbicide application. This research contributes to a comprehensive approach for the study of landraces under rainfed Mediterranean conditions, showing the benefits of growing these plant genetic resources from an agronomic perspective (maintaining yields while increasing protein content) but also from a sustainability approach (contributing to soil quality, weeds reduction, and cropland biodiversity).…”
Section: Grain Nitrogen and Straw Carbon Contentmentioning
confidence: 99%
“…Following the dawn of the green revolution, strenuous efforts to increase the adoption of agricultural innovations, such as improved varieties for wheat, rice, and maize, chemicals, machinery, and irrigation among producers resulted in a significant increment in incomes and global food output (Adhikari et al, 2018) especially in the global North as well as in emerging economies in Asia (Toenniessen, et al, 2008). However, in practice, the approach also brought environmental issues, health and social problems, monoculture, and the growth of unsustainable farming systems (Yapa, 1993;Dawson et al, 2016).…”
Section: Introductionmentioning
confidence: 99%